Penguatan Pendidikan Karakter pada Remaja untuk Mencegah Pergaulan Bebas di Desa Rejosari - Manzilatus Shofiy; A. Najid As Syafiq; Widad Nailu Salsabila; Kenanga Kurnia Putri; Zurika Estiyarika; Shona Zaidan Adib; Abdul Afif; Risda Sofiyatul Muna; Hamdan Husein Batubara (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Character education is a key element in the formation of morals and ethics in adolescents. In the midst of the challenges of globalization and increasingly rapid technological developments, teenagers are often faced with various negative influences, including promiscuity which can lead to deviant behavior. Strengthening character education for teenagers in Rejosari village and the family environment is very important to equip teenagers with moral values, independence and social responsibility. This research aims to examine the role of character education in preventing promiscuity among teenagers. This activity was carried out in Rejosari Village, Ngampel District, Kendal Regency with 30 participants. The research method used is descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The results of the research show that teenagers who receive strong character education are better able to avoid negative influences and have resistance to promiscuity. Effective implementation of character education requires collaboration between schools, families and communities to create an environment that supports positive character development in adolescents.